2012
DOI: 10.1007/s11661-012-1287-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microstructural Characterization of Thick Aluminum Plates Heavily Deformed Using Equal Channel Angular Extrusion

Abstract: A detailed quantitative analysis of the microstructure has been performed in three orthogonal planes of 15-mm-thick aluminum plates heavily deformed via two equal channel angular extrusion (ECAE) routes. One route was a conventional route A with no rotation between passes. Another route involved sequential 90 deg rotations about the normal direction (ND) between passes. The microstructure in the center of these plates, and especially the extent of microstructural heterogeneity, has been characterized quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…This approach has been previously applied for characterizing heterogeneity in microstructural refinement in samples deformed to large strains by either equal channel angular extrusion (ECAE) or compression [18][19][20][21]. The partitioning is based on the idea of detecting continuous areas within an EBSD map that have not been subdivided by boundaries of large misorientation angles, and such areas represent a heterogeneity in the effective refinement of the deformed microstructure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been previously applied for characterizing heterogeneity in microstructural refinement in samples deformed to large strains by either equal channel angular extrusion (ECAE) or compression [18][19][20][21]. The partitioning is based on the idea of detecting continuous areas within an EBSD map that have not been subdivided by boundaries of large misorientation angles, and such areas represent a heterogeneity in the effective refinement of the deformed microstructure.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has recently been shown [18] that the HAB fraction and the average boundary spacing do not always provide a good description of the extent of heterogeneity within a heavily deformed microstructure. In contrast, it has been demonstrated that partitioning of a deformed microstructure into subsets that contain either predominantly low angle misorientations or predominantly high angle misorientations can be used to provide a better quantitative characterization of microstructural heterogeneities in heavily deformed metals [18][19][20][21]. This approach is applied in the present work, where the microstructure and texture are examined over a large number of locations across the thickness of a nickel sample after 6 ARB cycles.…”
Section: Introductionmentioning
confidence: 99%
“…A model of GBS path according to Fu et al [14] (a) (b) Figure 3. Examples of unit cell models of nanocrystalline materials: Cubic unit cell model by Kim [17](a) and self-consistent polycrystal model by Jiang and Weng [33] presented as superposition of two linear problems. Reprinted with kind permission from Elsevier.…”
Section: Discussionmentioning
confidence: 99%
“…[1] While the effect of processing route on the microstructure and texture development in ECAE-deformed rods and bars has been investigated in a large number of publications [2][3][4][5][6] , only a few studies have been carried out for establishing this effect for ECAE-processed plates, for which new routes, different from those proposed for rod or bar samples, can be utilized. [7][8][9][10][11] In a recent work on AA1050 plates deformed by 8 ECAE passes either without rotation between passes (route A) or with 90 deg sequential rotations about the plate normal ND (route B C〈ND〉 ), [11] it was found that the microstructure obtained via route B C〈ND〉 was more refined than that obtained via route A.…”
mentioning
confidence: 99%
“…[11] The effect of the processing route on texture evolution in ECAE plates was investigated by Ferrasse et al [9,10] However, these authors considered a large number of orientation fibers differing from the shear-type fibers commonly adopted for characterizing ECAE textures, [2][3][4][5][6] which complicates a comparison of textures in their plate samples with those in rod samples described in many other publications. To better compare the general tendencies of texture evolution during ECAE of plates with those of rod samples, a modeling and experimental investigation of textures formed by ECAE has therefore been carried out and is described in the present work for commercial purity aluminum.…”
mentioning
confidence: 99%